40Ar/39Ar age constraints to MIS 5.5 and MIS 5.3 paleo-sea levels: implications for global sea levels and ice-volume estimation - Fabio Florindo; Fabrizio Marra; Mario Gaeta; Brian Jicha (PANGAEA, 2023)
We present ten 40Ar/39Ar age determinations, both on primary volcanic deposits and on detrital sanidine, which provide geochronologic control on the MIS 5.5 and MIS 5.3 sea-level indicators that occur at three coastal caves in the central Tyrrhenian Sea of Italy. Samples dated for the present work are as follows: - Two pumice clasts (MOSC-22, MOSC-37) extracted from the sand layers constituting the sedimentary fill of Moscerini Cave, recovered during the original archaeological excavations performed in the year 1949, stored at the IIPU (Istituto Italiano di Paleontolgia Umana) repository in Anagni (Frosinone, italy). These two samples were processed at the rare Gas Laboratory of the University of Wisconsin Madison in March, 2019. - One tephra layer (sample GDC-10) intercalated in the sedimentary fill of Capre Cave collected in June, 2021. - Seven sedimentary sand samples collected at Guattari Cave (GU-1, GU-5, GU-105, GU-116) in June, 2020, and at Capre Cave (GDC-6, GDC-8, GDC-0) in June, 2021 . These dates constrain the age of a Strombus-bearing biodetritic conglomerate associated with a tidal notch occurring at 9.5 m a.s.l. at Cape Circeo between 121.5±5.8 and 116.2±1.2 ka. Moreover, deposition of backbeach deposits intercalated in the sedimentary filling of Guattari and Capre coastal caves is bracketed in the interval 110.4±1.4 ka to 104.9±0.9 ka. Such deposits are directly correlated with a tidal notch at ~2.5 m associated with another biodetritic conglomerate at Cape Circeo. The latter is correlated with the adjacent marine terrace, occurring at 3-5 m in the coast between Capes Circeo and Anzio, for which a maximum age of 100.7±6.6 ka was previously reported. These data provide evidence for a maximum sea level around 9.5 m above the present sea level and a duration of MIS 5.5 highstand until 116 ka, in line with estimation from other regions in the world. In contrast, they suggest a maximum sea level during MIS 5.3 highstand that is similar to the present level, and only ~7 m lower than the MIS 5.5 highstand, challenging the reconstructions of the MIS 5 ice-sheet volumes and derived global sea levels that are based on the benthic oxygen isotope records.